CXCR4-tropic, but not CCR5-tropic, human immunodeficiency virus infection is inhibited by the lipid raft-associated factors, acyclic retinoid analogs, and cholera toxin B subunit - Kamiyama, H. (2016)
10.1089/aid.2012.0174